Evaluation of unmanned aerial vehicle tactics through the metrics of survivability. (October 2022) - Lunsford, Ian; Bradley, Thomas H
Aircraft survivability is a classical consideration of combat aircraft design and tactical development, but the fundamental model of aircraft survivability must be updated to be able to consider modern tactical scenarios that are applicable to unmanned aircraft. This paper seeks therefore to define the set of design tradeoffs and an evaluation of the tactical effectiveness for unmanned aircraft survivability. Traditional and modern survivability evaluation methods are presented and integrated into a computational simulation to create a probabilistic evaluation of unmanned aircraft survivability. The results demonstrate the development of design tradeoffs for a hypothetical unmanned C-130J Hercules against a single man-portable air defense system. The discussion focuses on the demonstration of the utility of this survivability evaluation framework for consideration of survivability in unmanned aerial vehicle (UAV) design, the utility of considering survivability in the design of multi-UAV configurations (including the loyal wingman and swarms), and the value of the probabilistic survivability model for multi-aircraft simulations.